THE PECULIARITIES OF COMPLEXATION OF DNA MACROMOLECULE WITH LOW MOLECULAR LIGANDS - Haroutiunian, S. G.; Vardanyan, V. I.; Dalyan, Y. B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The present review is devoted to the analysis of peculiarities of DNA complexation with reversibly and irreversibly binding ligands. Three classes of low molecular ligands with different types of binding were discussed. These types of ligands particularly are: bivalent transitional metal ions, porphyrin complexes, and zwitterionic amino acids. As irreversible binding ligands some Pt(II) and Ru(III) complexes were used. The systematization of the general patterns and revealing of specific differences in interaction of above mentioned ligands with double helix DNA is presented.
Keywords: DNA complexation; reversibly and irreversibly binding ligands; Pt(II) and Ru(III) complexes